INTEGRATION PROBLEMS OF PREPARATION OF PHYSICAL EDUCATION TEACHER INTO THE EUROPEAN EDUCATIONAL AREA - Volodymyr Omelyanenko (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2017)
This article describes the main points and problems of future physical education teachers, their preparation and the ways to achieve it. Theoretical analysis, generalization and comparison of normatively legal documents and scientifically methodical literature is conducted analyzing the problem occurring during professional process of education of physical training teacher. The basic points of professional preparation of future physical trainers and sports specialists in context of integration according to euro standards is outlined here: imperfection of the system of national student mobility, absence of choice programs for achieving associates and bachelors degrees, significant allocation of educational disciplines, short pedagogical practice, absence of material teacher compensation and pedagogical leaders. For realization of academic mobility of students the standard of higher education, educationally-professional program and base curriculum normative part that would be identical for all higher educational establishments (amount of credits, sequence of study of disciplines, graphic arts of educational process), is needed. During the transition of studies from one educational direction to another there must be reasonable limits. students of contiguous major should be allowed to get masters degree. The process of integration of educational disciplines in Ukraine, as a rule, carries mechanical character, that does not allow: to group material logically and compactly, to prevent duplication of educational material into a course, to shorten its volume; to generalize similar material from different areas into one theme; to attain knowledge integrity. Summarizing the tendencies of improvement of organization and realization of pedagogical practice in foreign higher educational establishments it is necessary to make the following changes to the process of pedagogical practice in Ukraine: duration of practice should be planned during a separate semester or school year in the final graduation year; partially share practice responsibility with the pedagogical school stuff with corresponding payment or school should include pedagogical practice results into teachers score during attestation; to include results of students pedagogical practice into final score during final state examination.